2017
DOI: 10.1111/epi.13963
|View full text |Cite
|
Sign up to set email alerts
|

Stroke‐like migraine attacks after radiation therapy: A misnomer?

Abstract: SummaryObjective: To understand the frequency of electrographic and clinical seizures in patients with stroke-like migraine attacks after radiation therapy (SMART), and determine whether SMART warrants comprehensive electroencephalographic (EEG) monitoring and aggressive seizure management. Methods: We searched our magnetic resonance brain imaging report database for all patients between

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 35 publications
4
31
0
2
Order By: Relevance
“…Hypotheses have included deranged autoregulation caused by endothelial damage and radiation vasculopathy, as well as some form of cerebral hyperexcitability leading to seizures, headache, and months of slow‐to‐recover neural impairment. Some studies have suggested that SMART should not be considered a distinct diagnosis and have hypothesized that it could be an expression of either migrainous phenomena or seizures unrelated to prior radiation [14, 15]. We agree that seizures are often a component of SMART syndrome; however, nearly half the patients in our study did not have epileptiform discharges while all had the characteristic radiological abnormalities and very similar clinical signs and symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…Hypotheses have included deranged autoregulation caused by endothelial damage and radiation vasculopathy, as well as some form of cerebral hyperexcitability leading to seizures, headache, and months of slow‐to‐recover neural impairment. Some studies have suggested that SMART should not be considered a distinct diagnosis and have hypothesized that it could be an expression of either migrainous phenomena or seizures unrelated to prior radiation [14, 15]. We agree that seizures are often a component of SMART syndrome; however, nearly half the patients in our study did not have epileptiform discharges while all had the characteristic radiological abnormalities and very similar clinical signs and symptoms.…”
Section: Discussionsupporting
confidence: 59%
“…Epileptic seizures may be related to SMART and may be underdiagnosed in this condition. 9 On the one hand, in our case, the presence of ischemia could represent another source of seizure trigger, given the far less severe SMART-related imaging changes compared to the initial presentation, when no seizures had occurred. On the other hand, fluctuating levels of consciousness had been reported to have occurred during a period of 2 weeks prior to the second admission, thus most likely before the ischemia.…”
Section: Discussionmentioning
confidence: 63%
“…In our case, the recurrent headache is most likely an expression of SMART itself. Epileptic seizures may be related to SMART and may be underdiagnosed in this condition . On the one hand, in our case, the presence of ischemia could represent another source of seizure trigger, given the far less severe SMART‐related imaging changes compared to the initial presentation, when no seizures had occurred.…”
Section: Discussionmentioning
confidence: 74%
“…Выявлена значительная экспрессия этих белков в нейронах и эндотелии мозга, вероятно потенцируемая эпилептической активностью, что может, в свою очередь, вызвать усиленный транспорт аминокислоты, преимущественно в нейроны [14]. Более того, включение в протокол обследования 6 больных с подозрением на SMART-синдром видео-ЭЭГ мониторинга, дало основание рассматривать этот феномен как потенциально эпилептический синдром [20]. Усиление транспорта аминокислот в эпилептогенном очаге установлено и при ПЭТ с 11 С-метионином [21].…”
unclassified
“…В настоящее время значимость эпилепсии и эпилептической активности мозга выходят на первый план в обсуждении SMART-синдрома. Его аббревиатура описывает приступы мигрени как основной спектр симптомов и оставляет без внимания наличие эпилептического процесса, который может играть более существенную роль в патогенезе, чем это представлялось ранее, поэтому само название кажется неправильным [20].…”
unclassified